Female Poets of World War I - Mohammed Salah Aldeen, Rand (Utopía y Praxis Latinoamericana, 2020)
ABSTRACTEvery citizen of Great Britain and the United States had their role during the First World War. Yet, Women were not allowed to be soldiers in front lines, as they were much needed into duties like nurses, ammunition workers, or as housemakers. Many of these women expressed their feelings about war through literature, especially poetry. However, their voices of WWI were often overlooked in comparison to those of male poets. This study sheds light on three of these female poets with reference to their poems about the First World War. These three poetesses are Jessie Pope, Muriel Stuart, and Katherine Tynan.